2010
DOI: 10.1128/aem.01505-10
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ethanol Productivity in Xylose-Utilizing Saccharomyces cerevisiae via a Randomly Mutagenized Xylose Reductase

Abstract: Baker's yeast (Saccharomyces cerevisiae) has been genetically engineered to ferment the pentose sugar xylose present in lignocellulose biomass. One of the reactions controlling the rate of xylose utilization is catalyzed by xylose reductase (XR). In particular, the cofactor specificity of XR is not optimized with respect to the downstream pathway, and the reaction rate is insufficient for high xylose utilization in S. cerevisiae. The current study describes a novel approach to improve XR for ethanol production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 42 publications
2
73
0
Order By: Relevance
“…Second, the overexpression of a heterologous transaldolase, encoded by tal1, from S. stipitis was chosen, since this protein has been previously reported to be beneficial for xylose utilization in S. cerevisiae (14). The overexpression of downstream pathway enzymes to ensure proper flux is advantageous for selection phenotypes (37). To achieve overexpression of tal1, the gene was cloned behind a TEF promoter in the p415 plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the overexpression of a heterologous transaldolase, encoded by tal1, from S. stipitis was chosen, since this protein has been previously reported to be beneficial for xylose utilization in S. cerevisiae (14). The overexpression of downstream pathway enzymes to ensure proper flux is advantageous for selection phenotypes (37). To achieve overexpression of tal1, the gene was cloned behind a TEF promoter in the p415 plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…However, this pathway is inherently limited by a cofactor imbalance with the xylose reductase-utilizing NADPH and the xylitol dehydrogenase-utilizing NAD ϩ , which leads to diversion of metabolic flux toward undesired products as a compensation reaction and decreases the ethanol yield (49). Recent work has focused on modifying the cofactor preferences of these enzymes to make them more compatible and to establish an oxidation-reduction cycle (37,47). However, even with matching cofactor specificities, the oxidoreductase pathway requires cofactors that may limit overall pathway throughput.…”
mentioning
confidence: 99%
“…However, S. cerevisiae lacks an endogenous xylose catabolic pathway and thus is unable to natively use the second most abundant sugar in lignocellulosic biomass. Decades of research have been focused on improving xylose catabolic pathways in recombinant S. cerevisiae (17)(18)(19)(20)(21)(22), but less work has been focused on the first committed step of the process-xylose transport, an outstanding limitation in the efficient conversion of lignocellulosic sugars (23,24).…”
mentioning
confidence: 99%
“…Although the identified functional enzymes were expressed in recombinant Saccharomyces cerevisiae industrial strains, their efficiency in fermenting xylose was shown to still be quite low [87,88], suggesting the requirement of additional modifications. Overexpression of genes encoding enzymes of non-oxidative pentose phosphate pathway (PPP) [89], replacement of a small amount of enzymes of xylose metabolism [90], as well as isolation of xylose transporters [91,92] were pointed out as crucial factors for the adequate function of this pathway. However, a more holistic approach could also provide the metabolic reconstruction of most biologically relevant and predictive models to improve the fermentative ability of S. cerevisiae [93].…”
Section: Microbial Metabolomicsmentioning
confidence: 99%